Two new species of Caulobothrium (Cestoda: “Tetraphyllidea”) from the duckbill eagle ray, Aetomylaeus bovinus (Myliobatiformes: Myliobatidae), off Senegal with new insights on morphological features of the genus - Caira, Janine N.; Jensen, Kirsten (Zootaxa, 2021)
Two new species of the cestode genus Caulobothrium, collected from the duckbill eagle ray, Aetomylaeus bovinus, off Senegal, are described. Although postulated as sister taxa in an earlier molecular phylogenetic analysis, Caulobothrium multispelaeum n. sp. and Caulobothrium katzi n. sp., respectively, are among the smallest and largest members of the genus. The smaller species is unique among its congeners in possessing unusual medial longitudinal grooves along the dorsal and ventral surfaces of its strobila that develop into a tandem series of elliptical apertures on the posterior proglottids. The inner surfaces of these apertures stained positively with McManus’ periodic acid Schiff in a manner similar to that seen in members of the distantly related lecanicephalidean genus Elicilacunosus. The larger species differs from its congeners in size, number of proglottids, and arrangement of bothridial loculi. Both new species were found to possess a small apical sucker on the anterior margin of each of their bothridia. Scanning electron microscopy (SEM) and frontal sections of a bothridium of Caulobothrium tetrascaphium suggests that this species also bears an apical sucker. Examination of the hologenophore of the species provisionally referred to as Caulobothrium n. sp. 5 in the earlier molecular analysis indicates it is conspecific with the recently described Caulobothrium pedunculatum, which was also determined to possess bothridial apical suckers. This leads us to suspect that this feature may be found to occur in all members of the genus. SEM of specimens of Caulobothrium for the first time indicates their bothridial surfaces are covered with filitriches of various sizes but lack spinitriches; spinitriches were seen only on the cephalic peduncle of C. katzi n. sp. The geographic distribution and host associations of Caulobothrium are expanded to include data now available for all species. The diagnosis of the genus is revised to include all of this information.